Peranan Statin Dalam Memperbaiki Fungsi Paru pada Penyakit Paru Obstruktif Kronik (PPOK) - Dina Fauzia (Jurnal Ilmu Kedokteran, 2016)
Chronic obstructive pulmonary disease (COPD) is a disease state characterized by airflow limitation that is not fullyreversible and a global health problem with an increasing incidence. Latest pathogenesis states that inflammationoccurs in COPD is not just limited to the airway and parenchymal lung disease, but a systemic inflammation involvingother systems, especially the cardiovascular system. Therefore, the approach to COPD therapy currently includes twoaspects, suppression of lung inflammation and systemic diseases. One of the the therapeutic agent that may affectboth aspects are statin.